1478Extreme daily numbers of general practice encounters of asthma and allergic rhinitis in Australia. (2nd September 2021) - Waudby, Charlotte; Osborne, Nicholas; Muscatello, David
Abstract: Background: Asthma affects approximately 11% of Australia's population and allergic rhinitis 19%. Grass pollen is associated with asthma and allergic rhinitis exacerbations. This study tested the hypothesis that days with extreme numbers of general practice (GP) encounters for asthma and allergic rhinitis aligned with grass pollen season. Methods: The MedicineInsight GP database contains longitudinal data on persons attending a sample of Australian GPs. We created time series of daily counts of asthma and allergic rhinitis encounters by state and territory to identify extreme encounter days; days with counts above the 99th percentile. Results: Of 3, 036, 678 attendances during the study period, 2.4% were for asthma. There were 83 extreme encounter days during April to December, across Australia. Victoria and South Australia had the highest increase in attendances on extreme days. Allergic rhinitis encounters represented 0.9% of attendances. Of the 69 extreme allergic rhinitis encounter days across Australia, Victoria and Australian Capital Territory had the highest increase in attendances. Allergic rhinitis extreme days were clustered between mid-October and early December (72%), compared to 22% of the asthma extreme days. Conclusions: Extreme asthma GP encounters were not as strongly associated with grass pollen season compared to allergic rhinitis encounters. Victoria had a high number of encounters on asthma and allergic rhinitis extreme days, many associated with thunderstorm asthma. Key messages: Extreme asthma encounter days can be associated with cooler months, grass pollen season and school holidays. Extremes allergic rhinitis presentation days were aligned with grass pollen season.